(untitled) (MCIT: Proceedings of International scientific and practical conference, 2019)
A set of key performance indicators (KPIs) for manufacturing operation management is introduced in the ISO 22400 standart. In this paper, a framework is introduced in order to solve the problem of dividing into types all the 38 KPIs.